PEMIKIRAN EKONOMI ISLAM M.A Mannan - Elvin Nurgulam Qurbani (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
Studies and research on Islamic economics have been growing again in recent decades. Many international forums on economics are held in various countries, such as conferences, seminars, symposiums, and workshops. Islamic economists in conventional economics and shari'ah, appear as speakers at these forums. M. A Mannan is one such thinker. This paper that discusses M. A Mannan's thoughts in Islamic Economics uses a research methodology based on library research. Starting with briefly discussing his life history, then this paper discusses Mannan's various thoughts on Islamic Economics. Then his views on consumption, production and income distribution. In addition, Mannan's thoughts on fiscal policy and spending in Islamic economics were also discussed, thoughts on zakat, and his thoughts on economic development planning in Islam.